Effects of land use change on amphibian community from Kianjavato forest station, south eastern Madagascar - Rodin, Raberanto; A.D., Razafindrazanakolona; Ashande, Colette Masengo; Ngbolua, Koto-Te-Nyiwa; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2024)
An assessment of amphibian species was carried out in the Forêt Classée de Kianjavato (FCK), part of the Dense Humid Evergreen Forests of eastern Madagascar. The research was carried out in two phases, first during the cool season (June - July 2012) and then during the wet season (November - December 2014), covering three types of habitat: deforested area, reforestation area and forest area. Three standard inventory methods were used: direct observation, systematic excavation and trapping. A total of 26 amphibian species were recorded, including one new to the site. Most of these species are classified as Least Concern by the IUCN, represented by low numbers of individuals. The distribution of amphibian species is influenced by biotic factors such as the structure of the vegetation cover. Amphibians are found in both forested and degraded areas. The degraded areas share several species, forming a habitat distinct from the forested area. The study highlights the extension of the range of distribution of amphibian species and emphasises that the conditions necessary for their presence in degraded areas are not yet in place. The FCK, with its varied ecological landscape, is crucial to the preservation of biological diversity in eastern Madagascar.